2019
DOI: 10.1007/s11682-019-00043-5
|View full text |Cite
|
Sign up to set email alerts
|

COMT-Val158Met polymorphism modulates antipsychotic effects on auditory verbal hallucinations and temporal lobe gray matter volumes in healthy individuals—symptom relief accompanied by worrisome volume reductions

Abstract: Investigation of auditory verbal hallucinations (AVHs) in schizophrenics is complicated by psychiatric symptoms. Investigating healthy individuals with AVHs (H-AVHs) can obviate such confounding factors. The objective of this study was to explore the effects of antipsychotic treatment on AVHs and gray matter volumes (GMVs) in H-AVH subjects and whether such are effects are influenced by COMT-Val158Met genotype. Magnetic resonance imaging (MRI) and genotyping studies were completed for 42 H-AVH subjects and 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…SNPs may influence the effect of antipsychotics. The COMT Val158Met substitution at the rs4680 loci effectively predicted dopaminergic drug effects, as the COMT inhibitor improved cognitive functions Val homozygotes, whereas the antipsychotics were more effective in Met homozygotes (Zhuo et al, 2019). Protein structure and function studies revealed that Val-Met substitution disrupts enzyme stability, leading to suppressed dopamine clearance and higher dopamine activity (Chen et al, 2004).…”
Section: Genetic Polymorphisms In the Dopamine System In Scz And Drugmentioning
confidence: 99%
“…SNPs may influence the effect of antipsychotics. The COMT Val158Met substitution at the rs4680 loci effectively predicted dopaminergic drug effects, as the COMT inhibitor improved cognitive functions Val homozygotes, whereas the antipsychotics were more effective in Met homozygotes (Zhuo et al, 2019). Protein structure and function studies revealed that Val-Met substitution disrupts enzyme stability, leading to suppressed dopamine clearance and higher dopamine activity (Chen et al, 2004).…”
Section: Genetic Polymorphisms In the Dopamine System In Scz And Drugmentioning
confidence: 99%
“…The efficacy of antipsychotic drugs in patients with schizophrenia has been indicated to be related to rs4680 SNP in COMT gene; associated with a decreased therapeutic effect, leading to pharmacotherapy resistance. In addition, the COMT interacts with several genes to produce various phenotypes [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%